Moderasi Beragama: Merawat Harmoni dan Kerukunan melalui Kunjungan ke Klenteng Eng An Kiong, Malang - ’inayatullah, Muhammad (Maliki Interdisciplinary Journal, 2025)
The moderation of religion is an important part of maintaining harmony among Indonesia’s diverse society, which has a variety of cultures, traditions, and beliefs. Through a visit to the Khong Hu Chu community at the Eng An Kiong Temple in Malang, students gained firsthand experience of how the values of tolerance, respect for ancestors, and openness are applied in everyday life. Observations of religious rituals, explanations of the roles of deities, and social interactions among community members show that religious moderation can grow through a comprehensive understanding of other cultures and spiritualities. This visit also showed that an inclusive attitude in Islam—through the values of tasamuh, rahmatan lil alamin, and the spirit of coexistence—can harmoniously coexist with the Khong Hu Chu community, thereby strengthening social harmony. This experience confirms that diversity is not an obstacle, but rather a treasure that can strengthen unity if managed through dialogue and mutual respect. Overall, this activity shows that religious moderation is not just a theoretical concept, but a real practice that can build harmony and peace in Indonesia’s pluralistic society.